1992
DOI: 10.22358/jafs/69902/1992
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diets containing different levels of structural fibre on intestinal length, dry matter content of digesta, biochemical indices and electrolyte concentration in blood serum of geese (Part IV)

Abstract: Two experiments were conduced in which White Italian geese were fed diets containing large proportions of ground cereals: maize, oats, barley or rye; dried grass, dried sugar beet pulp, field bean or pea as well as low-glucosinolate rapeseed oilmeal, from var. Jantar. The highest body weight gains Were obtained when ground oats and rapeseed oilmeal were included in the diet, the lowest, when dried beet pulp and rye were given. Favourable growth parameters go together with higher dry matter content and pH of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Pakulska et al (1995) reported that in such a system of fattening, at the age of 14 weeks geese fed forage and a diet containing 20% rye between 4 and 8 weeks of life and 40% in the consecutive 6 weeks weighed only 5% less than control geese. However, Wiliczkiewicz et al (1992) observed that geese fed a diet containing 50% rye as the only feed from weeks 3 to 11 of life grew 16% slower, used 19% more feed per kilogram of body weight gain, had a lower dry matter content in the digesta and thicker intestinal walls than control birds fed a wheat and barley diet.…”
Section: Introductionmentioning
confidence: 94%
“…Pakulska et al (1995) reported that in such a system of fattening, at the age of 14 weeks geese fed forage and a diet containing 20% rye between 4 and 8 weeks of life and 40% in the consecutive 6 weeks weighed only 5% less than control geese. However, Wiliczkiewicz et al (1992) observed that geese fed a diet containing 50% rye as the only feed from weeks 3 to 11 of life grew 16% slower, used 19% more feed per kilogram of body weight gain, had a lower dry matter content in the digesta and thicker intestinal walls than control birds fed a wheat and barley diet.…”
Section: Introductionmentioning
confidence: 94%